The Development of Integrated Science Process Skills and Analytical Thinking Ability for Grade 6 Students Using Problem-Base Learning with Mind Mapping - Thai-on, Natsinee; Tanunchaibutra, Dr.Prin (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
The objectives of the research were to develop grade 6 students’ Integrated science process skill and Analytical thinking abilities using Problem-based learning with Mind mapping so that students would have average score not less than 70% of total score. The target group consisted of 15 grade 6 students in Banna-udom School. The research design was Action Research. The research instruments categorized into 3 categorized ware: 1) experimental tools, 2) reflection tools, and 3) assessment tools. The results were summarized: The students had average of Integrated science process skill ability for 23.06 or 76.88 % of the total score, and there were 13 students or 86.66 % passed the criteria which was higher than defined criteria. And the students had average of Analytical thinking ability for 23.33 or 77.77 % of the total score, and there were 13 students or 86.66 % passed the criteria which was higher than defined criteria.